2010
DOI: 10.1177/0898264310378040
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Mortality in Older Hip Fracture Inpatients Admitted to an Orthogeriatric Unit in Oslo, Norway

Abstract: Almost one fourth of older hip fracture patients in this unit died within a year. The most important predictor was admittance from nursing home, which was associated with comorbidity and frailty. More attention to patients from nursing homes is needed in the health care system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
62
4
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(72 citation statements)
references
References 33 publications
(63 reference statements)
3
62
4
3
Order By: Relevance
“…This group of patients may accordingly lack the reserve capacity often necessary to cope with a double trauma of hip fracture and surgery. Other studies have described comorbidity, age, male sex, delayed surgery and cognitive impairment as some of the most important risk factors for mortality [22][23][24][25][26]. Time from fracture to surgery is the only factor we can influence; our aim has been to identify other preventable factors that increase mortality risk.…”
Section: Discussionmentioning
confidence: 99%
“…This group of patients may accordingly lack the reserve capacity often necessary to cope with a double trauma of hip fracture and surgery. Other studies have described comorbidity, age, male sex, delayed surgery and cognitive impairment as some of the most important risk factors for mortality [22][23][24][25][26]. Time from fracture to surgery is the only factor we can influence; our aim has been to identify other preventable factors that increase mortality risk.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have reported overall 1-year mortality rates between 18% and 31% with men generally having a higher mortality rate than women [1][2][3][4][5][6]. This large disparity was confirmed by a 2009 systematic review of excess mortality following hip fracture [7].…”
Section: Introductionmentioning
confidence: 98%
“…Compared with the general population, patients with end-stage renal disease have significantly higher mortality rates after hip fracture [9]. Poor hygiene in assisted care and hospital settings can also increase mortality rates after a hip fracture [10,11]. RA has also been a predictive factor for poor outcomes in several diseases.…”
Section: Introductionmentioning
confidence: 99%